The Anguish of Prado. Biographical outline of a Peruvian intellectual (1871-1921) - Montoya Vásquez, Paul (2021)
The essay proposes a biographical analysis of the Peruvian political-intellectual context, at the turn from the 19th to the 20th century, based on the written production and the institutional activity of the intellectual Javier Prado y Ugarteche, frequently considered as one of the introducers of the ‘positivist theses’ to the local milieu by the historiography of ideas. This study focuses on the family and personal projects, since they are members of the political and academic elite, and it is particularly embedded in the political and institutional history of the period.